Güncel Üroloji Çalışmaları V (Bahar) - Altun, Ertürk; Tok, Doğan Sabri; Loglı, Ridell; Hasırcı, Eray; Ceylan, Şule; Çolak, Fatih; Cincorop, Serdar; Atkın, Mehmet Sinan; Aksoy, Hamit Zafer; Akça, Görkem; Kazaz, İlke Onur and Atnallar, Göktuğ and Okatan, Ali Ertan and Karaoğlu, Olcay and Eryılmaz, Recep and Sarıhan, Muhammed Hamdi and Demir, Murat and Eryılmaz, Recep and Duman, Veli and Özcan, Serkan and Ertaş, Kasım and Kotan, Muhammed and Kabar, Mücahit and İleri, Fatih and Aydamirov, Mubariz and Karkın, Kadir (Academician Publishing Book DOI Portal, 2024)
-